2017
DOI: 10.4317/jced.53796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of salivary CD14 concentration with dental caries in young children

Abstract: BackgroundDental caries is a chronic disease among children and there is need for studies assessing the caries risk factors using saliva. This study aimed to evaluate the association of salivary soluble CD14 and dental caries in young children.Material and MethodsA cross-sectional study was done among 300, 3-6 year old school children of Udupi district. A total of 40 children who were caries free, with no past systemic illness or craniofacial anomalies and 40 children with dental caries with no history of dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
3
6
0
Order By: Relevance
“…Saliva plays a role in maintaining oral health and homeostasis because it has immunological and non-immunological content [16], [17]. Every change in salivary protein composition plays an important role in the etiology of oral disease and development of dental caries [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Saliva plays a role in maintaining oral health and homeostasis because it has immunological and non-immunological content [16], [17]. Every change in salivary protein composition plays an important role in the etiology of oral disease and development of dental caries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Every change in salivary protein composition plays an important role in the etiology of oral disease and development of dental caries [17]. The immune system in children develops with age and becomes more sensitive to various microbiota and different antigens [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some Authors observed a significant rise in salivary sCD14 in patients affected by dental caries [12]. Conversely, other studies indicated higher sCD14 levels in healthy subjects [13][14][15]. These conflicting findings highlight the need for further studies on large sample sizes to define the reliability of sCD14 as a biomarker for the detection of carious lesions.…”
Section: Introductionmentioning
confidence: 99%